Trans-Anethole Alleviates Subclinical Necro-Haemorrhagic Enteritis-Induced Intestinal Barrier Dysfunction and Intestinal Inflammation in Broilers - Yu, Caiyun; Wang, Dong; Tong, Yichun; Li, Qiming; Yang, Weiren; Wang, Tian; Yang, Zaibin (Frontiers in Microbiology, 2022)
This study investigated the alleviative potential of TA on the impaired intestinal barrier and intestinal inflammation, and regulatory effects on gut microbiota in broilers with subclinical necro-haemorrhagic enteritis (NE) challenge. Subclinical NE challenge led to a severe decline in the 21 d body weight (BW) and average daily gain (ADG), but an increase in feed conversion ratio (FCR) and intestinal lesion score of birds compared with controls (P < 0.05). Compared with subclinical NE group, TA administration group exhibited lower (P < 0.05) intestinal lesion score and crypt depth (CD), serum diamine oxidase activity and D-lactate concentration but higher (P < 0.05) intestinal tight junction protein expressions, villus height (VH), VH/CD, and numbers of proliferating cell nuclear antigen (PCNA)-positive cells. Administration of TA also inhibited (P < 0.05) the expression of intestinal pro-inflammatory cytokines including interleukin (IL)-1β, IL-8, interferon-gamma (IFN-γ) and tumor necrosis factor-alpha (TNF-α) but increased (P < 0.05) jejunal IL-10 and secretory immunoglobulin A (sIgA) concentration. TA inclusion also led to a remarkable reduction of intestinal NF-kappa-B inhibitor alpha (IκBα) degradation and nuclear factor kappa beta (NF-κB) translocation. Moreover, TA modulated the cecal microbiota abundance and diversity of NE birds, as confirmed by reducing the phylum Firmicutes and genera RuminococcaceaeUCG-014, Eubacteriumcoprostanoligenesgroup, and RuminococcaceaeNK4A214group when supplemented at 600 mg/kg, reducing genera Butyricicoccus, Oscillibacter, and Flavonifractor when supplemented at 400 mg/kg (P < 0.05). Supplementation of TA in broiler diets could alleviate subclinical NE infection by restoring intestinal barrier integrity, inhibiting NF-κB signaling pathway and modulating gut microbiota. 600 mg/kg of TA is the optimum concentration for ameliorating subclinical NE in broilers.